Hydrothermal carbonization of lignocellulosic biomass and effects of combined Lewis and Brønsted acid catalysts. (1st November 2020) - Evcil, Tolgahan; Simsir, Hamza; Ucar, Suat; Tekin, Kubilay; Karagoz, Selhan
Graphical abstract: Highlights: Hydrochar was produced from biomass without and with AlCl3 -HCl catalyst. The use of AlCl3 -HCl catalyst reduced the hydrochar yields. The formation of carbon spheres was observed only in catalytic runs. The highest heating value for hydrochar was 29.12 MJ.kg −1 . Abstract: This study is the first to investigate the effect of combined Lewis and Brønsted acid catalysts on the hydrothermal carbonization of fir wood samples; here, hydrothermal carbonization of fir wood–with and without catalyst–was performed. In non-catalytic runs, the effects of temperature and residence time on hydrochar yields were investigated; temperature significantly affected hydrochar yields, whereas residence time had very little effect. A gradual increase in temperature resulted in a decrease in hydrochar yields while increasing the carbon content of hydrochars. At all tested temperatures, the use of a catalyst led to a decrease in hydrochar yields. The highest heating value of 29.12 MJ kg −1 was obtained at the highest temperature (275 °C) and the longest residence time (24 h). The use of catalysts slightly decreased the heating values. The hydrochars were mainly in the class of lignite coal; hydrochar obtained at 275 °C and a residence time of 12 h–either with or without catalysts–was classified as bituminous coal. Irregular carbon sphere formation was observed at all temperatures tested in the catalytic runs; however, no carbon spheres were observed in the non-catalytic runs. XRD patterns of hydrochars from the non-catalytic runs were similar for temperatures of 225, 250 and 275 °C; the peak observed at 2θ of 22° broadened after HTC processing. In the catalytic runs, two new peaks at 2θ of 38° and 49° were observed, in addition to broadened peaks (2θ = 22°). The use of catalysts led to the formation of the secondary char.